1984
DOI: 10.1111/j.1365-3180.1984.tb00572.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ammonium sulphate and related salts on the phytotoxicity of dichlorprop and other herbicides used for broadleaved weed control in cereals

Abstract: Summary In glasshouse experiments, additions of 10–100 g 1−1 ammonium sulphate enhanced the phytotoxicity to broadleaved weeds and cereals of several water‐soluble herbicides applied post‐emergence in 75–300 1 ha−1 with hydraulic nozzles. Studies with dichlorprop potassium salt and chickweed Stellaria media (L.) Vill. examined interactions between ammonium sulphate and environmental, application and formulation factors. Simulated rainfall immediately after spraying greatly reduced dichlorprop activity, whether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0

Year Published

1985
1985
1996
1996

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 6 publications
2
13
0
Order By: Relevance
“…Ammonium sulfate applied with glyphosate increased control of some but not all weed species (26). Turner and Loader (30,31) suggested that ammonium salts increase the rate of herbicide penetration through leaf surfaces. Ammonium sulfate may have increased 14 Cpicloram absorption in leafy spurge by affecting plant rather than spray droplet characteristics.…”
Section: Ammonium Saltsmentioning
confidence: 99%
“…Ammonium sulfate applied with glyphosate increased control of some but not all weed species (26). Turner and Loader (30,31) suggested that ammonium salts increase the rate of herbicide penetration through leaf surfaces. Ammonium sulfate may have increased 14 Cpicloram absorption in leafy spurge by affecting plant rather than spray droplet characteristics.…”
Section: Ammonium Saltsmentioning
confidence: 99%
“…), 2,4-D (Sexsmith 1953), picloram (Turner and Loader 1972;Wilson and Nishimoto 1975), dichlorprop (Turner and Loader 1984) and glyphosate (Blair 1975;Suwunnamek and Parker 1975;Loader 1975, 1980;O'Sullivan et al 1981). Enhancement of a non-water-soluble herbicide with ammonium sulphate was first reported for sethoxydim (Chow and MacGregor 1983 For the other species, the leaf-stage at the time of treatment was 4, 3, 4 (canola); 3, 3, 4 (green foxtail) and 3, 4, 3 (wild oat) for 1984, 1985 and 1986, respectively.…”
mentioning
confidence: 99%
“…Wills and McWhorter (1985) cite other such examples. Ammonium sulfate has also been used to increase the phytotoxicity of some herbicides used in forestry, including the potassium salt of picloram (4-amino-3,5,6-trichoro-2-pyridinecarboxylic acid) (Turner and Loader 1972) the isopropylamine salt of glyphosate (Turner and Loader 1975O'Sullivan and others 1980) and the potassium salt of dichlorprop [( f )-2-(2,4-dichlorophenoxy) propanoic acid] (Turner and Loader 1984). Szabo and Buchholtz (196 1) demonstrated that leaf penetration of the triethanolamine salt of 2,4-D [(2,4-dichlorophenoxy) acetic acid] increased with addition of ammonium nitrate and disodium phosphate.…”
Section: Introductionmentioning
confidence: 99%